1994
DOI: 10.1038/ng1294-328
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the TSC2 and PKD1 genes associated with severe infantile polycystic kidney disease — a contiguous gene syndrome

Abstract: Major genes which cause tuberous sclerosis (TSC) and autosomal dominant polycystic kidney disease (ADPKD), known as TSC2 and PKD1 respectively, lie immediately adjacent to each other on chromosome 16p. Renal cysts are often found in TSC, but a specific renal phenotype, distinguished by the severity and infantile presentation of the cystic changes, is seen in a small proportion of cases. We have identified large deletions disrupting TSC2 and PKD1 in each of six such cases studied. Analysis of the deletions indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
205
1
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(222 citation statements)
references
References 22 publications
7
205
1
5
Order By: Relevance
“…Disruption of both TSC2 and PKD1 genes is associated with a severe renal phenotype presenting in infancy. 21,22 These patients have bilateral polycystic renal disease and often grossly enlarged kidneys. Hence, the PKD is more severe than that associated with mutation to just PKD1, which normally results in adult onset disease; suggesting a synergistic role for the PKD1 and TSC2 products in cyst development.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of both TSC2 and PKD1 genes is associated with a severe renal phenotype presenting in infancy. 21,22 These patients have bilateral polycystic renal disease and often grossly enlarged kidneys. Hence, the PKD is more severe than that associated with mutation to just PKD1, which normally results in adult onset disease; suggesting a synergistic role for the PKD1 and TSC2 products in cyst development.…”
Section: Discussionmentioning
confidence: 99%
“…16 and 4, for ADPKD 1 and ADPKD 2 respectively to those of MFS and CCA, is worth noting and chromosomal crossovers cannot be ruled out. In tuberous sclerosis, large deletions, disrupting PKD 1 and the adjacent tuberous sclerosis type 2 gene (TSC 2) occurs, resulting in tuberous sclerosis and severe, childhood-onset polycystic kidney disease (15). So far, this has been the only clear description of a genotype/phenotype correlation in ADPKD and there are no reports of specific PKD 1 or PKD 2 mutations specifically predisposing to additional connective tissue abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A contiguous gene syndrome involving deletions of PKD1 and TSC2 has also been described where patients develop severe early-onset PKD with ESRF in childhood. 43 In the PKD1 gene, the location of the mutation appears to influence the disease severity with mutations in the 5 0 portion of the gene (0 -7812 nt) associated with a lower Polycystic kidney disease C Boucher and R Sandford mean age of ESRF than those 3 0 of 7812 nt. 44 In addition, it has been shown that a population of PKD1 patients presenting with a vascular phenotype have a median position of mutation located more 5 0 than a control population.…”
Section: Mutationsmentioning
confidence: 99%